2022
DOI: 10.1186/s13256-022-03420-9
|View full text |Cite
|
Sign up to set email alerts
|

Adenomatoid mesothelioma arising from the diaphragm: a case report and review of the literature

Abstract: Background Adenomatoid mesothelioma is a rare subtype of malignant mesothelioma that can be confused with adenomatoid tumors, which are classified as benign. The clinical features and optimal management of adenomatoid mesothelioma have not been elucidated in the literature. In this report, we present an extremely rare case of adenomatoid mesothelioma that developed on the peritoneal surface of the diaphragm as well as a literature review of adenomatoid mesothelioma in the abdominal cavity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Adenomatoid features are much less common in peritoneal mesothelioma 3–5 . A review of the literature reveals seven cases of peritoneal mesothelial neoplasms reported as adenomatoid mesothelioma, microcystic mesothelioma, or multifocal mesothelial adenomatoid tumors 55–61 . However, some of these cases were associated with conventional mesothelioma component, 55 and accompanying genetic analysis was not described.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adenomatoid features are much less common in peritoneal mesothelioma 3–5 . A review of the literature reveals seven cases of peritoneal mesothelial neoplasms reported as adenomatoid mesothelioma, microcystic mesothelioma, or multifocal mesothelial adenomatoid tumors 55–61 . However, some of these cases were associated with conventional mesothelioma component, 55 and accompanying genetic analysis was not described.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] A review of the literature reveals seven cases of peritoneal mesothelial neoplasms reported as adenomatoid mesothelioma, microcystic mesothelioma, or multifocal mesothelial adenomatoid tumors. [55][56][57][58][59][60][61] However, some of these cases were associated with conventional mesothelioma component, 55 and accompanying genetic analysis was not described. The tumor reported by Mori et al as adenomatoid peritoneal mesothelioma in a 64-year-old woman was strikingly adenomatoid, but the lung metastases resected 4 years later were more akin to conventional solid epithelioid mesothelioma.…”
Section: Discussionmentioning
confidence: 99%